2023
DOI: 10.1002/ecs2.4698
|View full text |Cite
|
Sign up to set email alerts
|

The role of short‐term temperature variability and light in shaping the phenology and characteristics of seagrass beds

Melisa C. Wong,
Michael Dowd

Abstract: Seagrass beds inhabit highly heterogeneous temperature regimes that characterize the marine nearshore. Temperature directly influences seagrasses and also provides indirect information on other ecologically relevant environmental variables. Multiple temperature processes operate on seasonal and sub‐seasonal timescales (i.e., hours to months) and include variation from seasonal air–sea heat fluxes, advective heat transport from upwelling and tidal circulation, and daily heating and cooling of shallow waters. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…5 and 23°C) and maximum growing degree day (GDD, i.e. heat accumulation) (Wong & Dowd, 2023). A partial RDA controlling for geography (latitude and longitude) was also conducted (RDA NS‐COND ), as was an RDA using only geography and no climate variables (RDA NS‐GEO ) to examine the proportion of total genetic variance in each set of predictors explained.…”
Section: Methodsmentioning
confidence: 99%
“…5 and 23°C) and maximum growing degree day (GDD, i.e. heat accumulation) (Wong & Dowd, 2023). A partial RDA controlling for geography (latitude and longitude) was also conducted (RDA NS‐COND ), as was an RDA using only geography and no climate variables (RDA NS‐GEO ) to examine the proportion of total genetic variance in each set of predictors explained.…”
Section: Methodsmentioning
confidence: 99%
“…GDD quantifies heat accumulation over time in a system and has been shown to influence eelgrass productivity and resilience (Krumhansl et al, 2021, Wong andDowd 2023). Here, GDD from model predictions and from in-situ observations is estimated by:…”
Section: Eelgrass Specific Temperature Metricsmentioning
confidence: 99%
“…Previous work has shown that temperature effects on eelgrass are multi-faceted, with multiple short-term (i.e., seasonal and sub-seasonal) temperature processes acting concomitantly (Krumhansl et al 2021). Eelgrass productivity and resilience tends to be lower in warm and highly variable temperature regimes where heat accumulates quickly and thermal physiological thresholds are exceeded (Krumhansl et al 2021, Wong andDowd 2023). Furthermore, eelgrass is also susceptible to marine heatwaves that originate offshore but propagate into, and are exacerbated by, nearshore conditions (Marbà and Duarte, 2010;Moore et al, 2014;Strydom et al 2020;Wiberg, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation